Application of PCR-RFLP method to determine polymorphism in BMP-15 and GDF9 fecundity genes in Northeast Bulgarian Merino sheep breed - Bozhilova-Sakova, Milena; Dimitrova, Ivona (Journal of BioScience and Biotechnology, 2021)
The purpose of this study was to determine the presence or absence of mutations in BMP-15 and GDF9 fecundity genes. In this experiment 60 ewes from Northeast Bulgarian Merino sheep breed were tested for polymorphisms in BMP-15 gene and SNP G1 of the GDF9 gene. This is the first investigation of BMP-15 gene by PCR-RFLP method in Bulgarian sheep breed. After DNA extraction and PCR amplification were received the expected PCR products. The digestion with restriction enzyme HinfI for BMP-15 gene and HhaI for GDF0 revealed mutations in both genes. In BMP-15 were found alleles + and G with frequencies 0.94 and 0.06, respectively and genotypes ++ and G+ with frequencies 0.80 and 0.12, respectively. In GDF9 were identified alleles G and A with frequencies 0.94 and 0.06 and genotypes GG and AG with frequencies 0.88 and 0.12.